(untitled) (Acta Polytechnica CTU Proceedings, 2017)
A netgraph is a graphical representation of a periodic timetable concept for given spatial or modal scope. It adds a third dimension to the network plan – time. Despite no strictly prescribed rules, a common practice notation has been settled over time. The authors propose an extension of a netgraph for planning of periodic railway capacity and operation, including related notation rules.